Case study: Czech service quality system - a tool for raising quality in services - Novotná, Jana; Chlopčík, Tomáš; Škodová Parmová, Dagmar (Verlag der GUC - Gesellschaft für Unternehmensrechnung und Controlling m.B.H., 2019)
Services represent an important source of economic growth. The essence of services is based on the fact, that services should be provided at the best possible level - with the highest quality. In the most general sense, quality can be understood as a satisfying of customer's expectations. In relation to tourism thus quality plays a crucial role and especially for organizations which implement appropriate tools to increase quality in their day-to-day activities, quality represents a significant competitive advantage. It is therefore necessary to pay special attention to quality as such and to the management of quality. ln conditions of the Czech Republic are these management tools represented by Czech Service Quality System and Hotelstars Union System. Both these systems bring and raise the quality and competitiveness in the field of tourism in the Czech Republic. The Czech Service Quality System is set up as a two-step system, suitable for SMEs in private as well as in the public sector. Successful certification is subject to the fulfillment of several entry conditions. The same applies to the Hotelstars Union System, which is the official uniform classification of accommodation facilities in the Czech Republic. The aim of this article is to introduce both system and to describe how the conditions are set and how the systems work, Special attention is focused on the Czech Service Quality System. The partial goal is to verify the applicability of the Czech Service Quality System in practice thru the comparison with Hotelstars Union system. Results of the mutual comparison will be presented in the conclusion chapter.
Keywords: tourism; services; raising quality; quality management